Cloud audit toolkit for financial regulators - Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
Drawing on existing practices observed by leading regulators from across the globe, this toolkit provides a comprehensive framework for improving supervisory work processes. It also includes a checklist that will help regulators to conduct an initial review of their existing oversight mechanisms.
Introduction - - Service Provider Oversight - - Physical and Logical Audit and Inspection Rights - - Security and Cybersecurity Requirements - - Data Protection and Privacy - - Data Governance, Retention, and Exit Strategy
- - Business Continuity and Disaster Recovery Planning - - Incident Response Requirements and Responses - - Standards, Certifications, and Global Best Practices - - Appendix.
Keywords: Auditing -- Data processing .; Cloud computing; Financial services industry -- Evaluation; Electronic book